Hemmkörperentwicklung bei Hämophilie-Patienten nach Präparate wechsel - Kocher, S.; Asmelash, G.; Makki, V.; Müller, S.; Krekeler, S.; Alesci, S.; Miesbach, W. (Hämostaseologie, 2012)
The retrospective observational study surveys the relationship between development of inhibitors in the treatment of haemophilia patients and risk factors such as changing FVIII products. A total of 119 patients were included in this study, 198 changes of FVIII products were evaluated. Results: During the observation period of 12 months none of the patients developed an inhibitor, which was temporally associated with a change of FVIII products. A frequent change of FVIII products didn’t lead to an increase in inhibitor risk. The change between plasmatic and recombinant preparations could not be confirmed as a risk factor. Furthermore, no correlation between treatment regimens, severity, patient age and comorbidities of the patients could be found.
Keywords: Haemophilia A; inhibitor; change of FVIII product